The Bauhaus for us: Interview with Anna Szigethy - Szabó, Zsófia (ARTCADIA, 2022)
Anna Szigethy DLA, visual artist, curator, associate professor at the Rippl-Rónai Art Institute of MATE, Kaposvár. In the academic year 2018/2019 she was one of the main organisers of the Bauhaus programme in Kaposvár. In this interview she was asked about the inspirations and typical themes of her art. She talked about her travels and experiences abroad, the transience of urban spaces, home and homelessness, the concepts which she tries to capture in her artworks. As well as talking about her current work and upcoming exhibitions, she also looked back on the past: the most memorable moments and projects of the Bauhaus anniversary.
Keywords: interview; artist; Bauhaus centenary; personal and school projects